Humans in the Traditional Ceremony of Sukat and Its Relevance to the Church's Pastoral Work in the Middle of the Tonyooi-Benuaq Tribe - Samdirgawijaya, Wilfridus (Educationist: Journal of Educational and Cultural Studies, 2022)
Humans always try to build relationships. The relationships that humans build include relationships with others, the universe and with the Creator. This study discusses the theological reflection on humans and the value of order-harmony in the Sukat custom and its relevance to the teachings of the Catholic Church. So, the approach used is a qualitative approach with literature and empirical research methods. The results of this study recommend: (1) The Sacramental Dimension in the Sukat Traditional Ceremony: an inculturative reflection to affirm the existence of the sacraments in the Catholic Church, (2) The role of traditional leadership and the Church: a pastoral review in preserving culture and indigenizing the Catholic Church among ethnic groups Dayak Tonyooi-Benuaq; (3) The concept of harmony in adat Sukat in relation to the story of creation: a biblical review of the Tonyooi-Benuaq culture and its relevance to the pastoral of the Church.